More Than Just Cleaning: Ubiquitin-Mediated Proteolysis in Fungal Pathogenesis - Cao, Chengjun; Xue, Chaoyang (Frontiers in Cellular and Infection Microbiology, 2021)
Ubiquitin-proteasome mediated protein turnover is an important regulatory mechanism of cellular function in eukaryotes. Extensive studies have linked the ubiquitin-proteasome system (UPS) to human diseases, and an array of proteasome inhibitors have been successfully developed for cancer therapy. Although still an emerging field, research on UPS regulation of fungal development and virulence has been rapidly advancing and has generated considerable excitement in its potential as a target for novel drugs. In this review, we summarize UPS composition and regulatory function in pathogenic fungi, especially in stress responses, host adaption, and fungal pathogenesis. Emphasis will be given to UPS regulation of pathogenic factors that are important for fungal pathogenesis. We also discuss future potential therapeutic strategies for fungal infections based on targeting UPS pathways.